Attitude of patients with schizophrenia towards antipsychotic therapy: Odnos pacientov s shizofrenijo do antipsihotične terapije - Kores Plesničar, Blanka; Gselman, Martin; Rajh, Simon; Zalar, Bojan (Acta Medico-Biotechnica, 2021)
Purpose: The failure to take medication as prescribed is a vexing problem for clinicians in all specialities, but especially in psychiatry. Schizophrenia is a chronic illness, so treatment adherence has a major influence on achieving and maintaining clinical remission. The patient’s attitude towards medication may predict adherence and is a major prognostic factor. We compared the attitudes toward antipsychotic medication in two treatment groups, schizophrenia patients receiving daily oral antipsychotics and those receiving monthly depot injections.Methods: Our study included 55 patients with schizophrenia or schizoaffective disorder as determined by the International Classification of Disease 10 (ICD 10). Patients receiving either daily oral antipsychotics (N=25) or monthly depot injections (N=30) completed the Drug Attitude Inventory–30 (DAI– 30) to compare subjective attitudes towards medication. Attitudes toward medication were also compared against social, occupational, and interpersonal functioning as determined by the Global Assessment of Functioning scale (GAF).Results: There was no statistically significant difference in total DAI–30 score between the patients taking oral antipsychotics and those receiving monthly depot injections (p=0.146). General attitudes towards antipsychotic medication were positive in both patient groups. There was no statistically significant co–relation between the DAI– 30 total score and everyday functioning between groups (p=0.299).Conclusion: The attitude towards medication is an important factor in treatment compliance in patients with schizophrenia. Attitudes were positive and did not depend on dosing method, indicating that choice of treatment should be based on clinical efficacy as neither dosing method was associated with a greater risk of noncompliance.
Keywords: schizophrenia; Drug Attitude Inventory; Global Assessment of Functioning; subjective response; treatment adherence; antipsychotics